A paixão de Vincent: um estudo sobre o sofrimento de Vincent van Gogh - Alexmovitz, Guilherme Aparecido Costa (2012)
Due to the geniality and tragic history of the Dutch painter Vincent van Gogh, psychiatrists, psychologists, and scholars from around the world have written several works in order to explain the suffering that culminated in his suicide. The present work aims to approach that suffering through the existential-phenomenology approach, which allows one to understand the suffering of the painter from his own life experience. A total of one hundred and fifty-six letters sent to his brother Théo, from 1872 to 1880, was analyzed and understood through Martin Heidegger s concept of attunement, which allowed the understanding of suffering as a way of being in the world. From this theoretical framework, I elected three possible forms of the artist s suffering different attunements that were present in several moments of this particular period of his life: the weight of the other, nostalgia, and fanaticism. The result of the analysis pointed to the existential meaning behind the painful Van Gogh s way of being in the world: the search for belonging